2013
DOI: 10.1016/j.bone.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality after hip fracture among the elderly in Taiwan: A nationwide population-based cohort study

Abstract: Osteoporotic hip fractures cause high mortality in the elderly population. However, few population studies reported the long-term mortality of hip fracture among the elderly in Asian population. This study assessed the incidence, excess mortality, and risk factors after osteoporotic hip fractures through inpatients aged 60 years or older. A total of 143,595 patients with hip fracture were selected from Taiwan National Health Insurance database in the years 1999 to 2009 and followed up until the end of 2010. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 44 publications
11
76
2
3
Order By: Relevance
“…Our current study showed that the female gender had higher SMRs in the younger age groups (50-69 years old) but lower ratios in the older age groups (over age 80). These findings were similar to those reported in Taiwan [26]; the authors of that study suspected that the withdrawal effect of estrogen after menopause would be more pronounced in the younger Asian females.…”
Section: Mortality and Smr After Hip Fracturessupporting
confidence: 90%
See 2 more Smart Citations
“…Our current study showed that the female gender had higher SMRs in the younger age groups (50-69 years old) but lower ratios in the older age groups (over age 80). These findings were similar to those reported in Taiwan [26]; the authors of that study suspected that the withdrawal effect of estrogen after menopause would be more pronounced in the younger Asian females.…”
Section: Mortality and Smr After Hip Fracturessupporting
confidence: 90%
“…We calculated SMRs to indirectly compare the excess mortality rates after hip fracture with those in the general population. Our current study showed that the average SMR 1 year after hip fracture was 10.9 (men: 11.9, women: 11.2), similar to the ratio in Taiwan (9.67) but higher than that in Western countries [26,[29][30][31]. Gender-specific SMRs were found to be consistently higher in males than in females for all age groups in Western countries [31,32].…”
Section: Mortality and Smr After Hip Fracturessupporting
confidence: 77%
See 1 more Smart Citation
“…The increased excess mortality in women compared with men was obvious immediately after the hip fracture operation, persisting surprisingly until the end of the 11-year follow-up. In most of the previous studies, the mortality rates were higher in men than in women [1,[31][32][33]. The opposite result has also been published.…”
Section: Discussionmentioning
confidence: 54%
“…7 Þrjátíu daga dánartíðni eftir innlögn eða aðgerð er um 8-10% 4,6 og eins árs dánartíðni milli 16-30%. 3,[22][23][24] Dánartíðnin er haerri hjá körlum en konum, 3,4,6 um 30% á móti 20% einu ári eftir brot. 3 Tilgangur þessarar rannsóknar var að gefa yfirlit um meðferð og afdrif sjúklinga sem mjaðmarbrotna og gangast undir aðgerð á Landspítala með sérstakri áherslu á bið eftir aðgerð, búsetu eftir útskrift af sjúkrahúsi og dánartíðni einu ári eftir mjaðmarbrot.…”
Section: áGripunclassified